2022
DOI: 10.1155/2022/4808806
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of ANCA-Associated Vasculitis at a Tertiary Healthcare Facility

Abstract: Purpose of the Study. Antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) is a rare multisystem autoimmune condition with an incidence of 0.4–24 per 1 million person- years. The severity of renal involvement predicts prognosis. Limited data are available on its management and outcomes; thus, we aim to assess this at our tertiary-care renal facility. Study Design. Retrospective data were collected using our national renal electronic database (eMED) to identify AAV patients over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a prospective study on the RAVE trial’s patients, using RTX showed promising results with a safe and more effective outcome in relapsed patients who were treated with either RTX or CYC [ 40 ]. In another comparative study of RTX and CYC on 16 GPA and 20 MPA patients, RTX was favorable for the induction of remission in the refractory AAV patients [ 96 ]. RTX is considered a promising treatment for elderly patients due to the higher risk of treatment-related side effects in AAV patients under CYC or GC treatment [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study on the RAVE trial’s patients, using RTX showed promising results with a safe and more effective outcome in relapsed patients who were treated with either RTX or CYC [ 40 ]. In another comparative study of RTX and CYC on 16 GPA and 20 MPA patients, RTX was favorable for the induction of remission in the refractory AAV patients [ 96 ]. RTX is considered a promising treatment for elderly patients due to the higher risk of treatment-related side effects in AAV patients under CYC or GC treatment [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…CR was achieved in 93% of the RTX group and 70% in the conventional group; however, no significant difference was observed between these two groups in 6-month and 12-month renal recovery. Another study on 36 AAV patients with renal involvement showed that RTX is a favorable induction agent in relapsed AAV patients, and 41.7% and 28.6% of AAV patients under CYC and RTX faced ESRD or death, respectively [ 96 ]. Moura et al [ 98 ] investigated the efficacy of RTX and CYC in 251 patients with severe disease and showed that no significant difference was observed between RTX and CYC in the induction of remission.…”
Section: Resultsmentioning
confidence: 99%
“…Their incidence increases with age, reaching a high level in the 60-70-year-old age group. 6,7 Immunosuppressive drugs are used to induce remission and for long-term maintenance therapy. Cyclophosphamide or rituximab with glucocorticoids is recommended as induction therapy for severe life-threatening AAV.…”
Section: Introductionmentioning
confidence: 99%